Higher-order Network Analysis of Fine Particulate Matter (PM2.5) Transport in China at City Level. Issue 1 (December 2017) - Wang, Yufang; Wang, Haiyan; Chang, Shuhua; Liu, Maoxing
Abstract Specification ofPM 2.5 transmission characteristics is important for pollution control and policymaking. We apply higher-order organization of complex networks to identify major potentialPM 2.5 contributors andPM 2.5 transport pathways of a network of 189 cities in China. The network we create in this paper consists of major cities in China and contains information on meteorological conditions of wind speed and wind direction, data on geographic distance, mountains, andPM 2.5 concentrations. We aim to revealPM 2.5 mobility between cities in China. Two major conclusions are revealed through motif analysis of complex networks. First, major potentialPM 2.5 pollution contributors are identified for each cluster by one motif, which reflects movements from source to target. Second, transport pathways ofPM 2.5 are revealed by another motif, which reflects transmission routes. To our knowledge, this is the first work to apply higher-order network analysis to studyPM 2.5 transport.